2019
DOI: 10.3390/cancers11121977
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Single-Nucleotide Polymorphisms in Pituitary Adenomas Tumorigenesis

Abstract: Pituitary adenomas (PAs) are among the most common intracranial neoplasms, but despite their histologically benign nature, these tumors sometimes grow large enough to cause symptoms of mass effect such as vision loss, headaches, or hypopituitarism. When they get this large, surgery will unfortunately not be curative and, other than prolactinomas, medical options are limited, and radiation has variable efficacy in controlling growth. Understanding the genetic perturbations, such as single nucleotide polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…And individual genetic factors play an important role. Single nucleotide polymorphism (SNP) refers to the polymorphism of DNA sequence caused by the variation of a single nucleotide in the genome, which is the most common form of human genetic variation, accounting for more than 90% of all known polymorphisms [1]. Single nucleotide polymorphisms (SNPs) can regulate gene function and expression and has become an effective tool and means of genetic research.…”
Section: Introductionmentioning
confidence: 99%
“…And individual genetic factors play an important role. Single nucleotide polymorphism (SNP) refers to the polymorphism of DNA sequence caused by the variation of a single nucleotide in the genome, which is the most common form of human genetic variation, accounting for more than 90% of all known polymorphisms [1]. Single nucleotide polymorphisms (SNPs) can regulate gene function and expression and has become an effective tool and means of genetic research.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, advanced techniques have allowed the exploration of either mono-omic or multi-omics, such as genomic, transcriptomic, epigenomic, metabolomic, proteomic, and lipidomic, to study the characteristics of NFPAs [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Though attempts to explore the underlying mechanism of invasiveness and aggressiveness of SCAs are still limited and inconclusive, we have already witnessed some advances, especially those using various -omics approaches to provide novel insights into the invasive and aggressive behavior of SCAs.…”
Section: Pathogenesismentioning
confidence: 99%
“…Resection is rst-line treatment for aggressive GHSPAs but is usually suboptimal. Some studies have shown that the recurrence prevalence of aggressive GHSPAs may be as high as 10-30% even if the GHSPA is resected completely [4].…”
Section: Introductionmentioning
confidence: 99%